Letter - Winstanley, E.
032-0042-001 Telegraphic Address: INLAND-"WHOLESALE, MANCHESTER." FOREIGN-"COPEXPORT, MANCHESTER." TELEPHONE: BLACKFRIARS 1212. EXTENSION NO. 87 PLEASE ADDRESS YOUR REPLY: CO-OPERATIVE WHOLESALE SOCIETY LIMITED, EXPORTERS, BUYING AND SHIPPING AGENTS. 1 . BALLOON STREET. MANCHESTER, 4. CABLE CODES A.B.C. 6TH AND 7TH EDITIONS: WESTERN UNION 8 LETTER: BENTLEY COMPLETE PHRASE: BENTLEY SECOND PHRASE: A.1. MARCONI, AND PRIVATE. Our Reference: Export 2968 ST/RN. Your Reference: HVT/EAB. 30th May, 1939. The Trades Union Congress, Transport House, Smith Square, LONDON S.W.1. Dear Sirs, We have received your letter of the 26th instant, enclosing provisional list of Footwear which is being delivered for shipment by the s.s. C.W.S. PROGRESS, to Rouen. You may be sure that, in the event of any other packages coming forward, which are not included on the list, the whole of the goods will be placed on one Bill of Lading. We are having this document made out in duplicate, in the name of the Co-operative Wholesale Society, Ltd., Rouen, who will be effecting clearance upon arrival, but will send one copy forward to Mr. W. Schevenels, Paris, who will be responsible for the forwarding arrangements from Rouen to ultimate destination. We have asked our Depot to communicate with Mr. Schevenels upon arrival of the goods. Yours faithfully, E. Winstanley, Export Department. 292/946/32/42